Analysis of the Hydrological Functioning of the Oued Reghaya Watershed in the Context of Climate Change (Tensift, Morocco) - Choukri Bahija; Benchattou Abdelmoumen; Ourabit Souad; El Ghachi Mohamed (African Journal of Advanced Pure and Applied Sciences, 2023)
From global to local, climate change has become a political, social, and major problem for the 21st century [1]. Through several studies of future climate projections, Morocco has been exposed to a series of dry periods, making it vulnerable to climate change [2]. The Reghaya sub-basin is located in the High Atlas of Marrakech; it covers an area of 306 km2 and is considered one of the most important sub-basins of the Oued Tensift. Although the watershed is receiving rainfall and snowfall at high altitudes, the study basin is experiencing very frequent hydrological disturbances. In this sense, we have chosen to study the flows recorded by the Tahanaout hydrometric station, located downstream of the watershed, to extract the hydrological cycles (low and high water) using the determination of the monthly flow coefficient. The hydrometric study of the Oued Reghaya watershed, shows that the flows recorded by the station of Tahanaout have a significant temporal variation. Generally, low water periods are marked in the summer and autumn months, whereas high water periods are marked in the winter and spring months. This work shows that the hydrological regime of the Oued Reghaya watershed is rainy, which makes it vulnerable to events